(untitled) (Research, Society and Development, 2022)
This study aims to analyze the knowledge of oral cancer among students of the Maurício de Nassau University Center, Graças unit, seeking to minimize the difficulties in recognizing oral cancer and potentially malignant oral lesions. A cross-sectional observational research with a quantitative approach was carried out among students from the 4th to the 10th period of the dentistry course. A questionnaire on the Google Forms platform was used for data collection. For data analysis, absolute and percentage distributions, statistical and association measures were obtained. The result obtained in our study shows a lack of preparation of the students in recognizing self-evaluation practices, as well as diagnosis and effective guidance to the patient, even in advanced periods of the dental course. It was possible to verify that the level of knowledge of the dental students at the Maurício de Nassau University Center is insufficient. The inconsistency of some findings reinforces the importance of investing in measures and conducts that contribute to the formation and training of dental students.